A strategy utilizing ambulatory monitoring and home and clinic blood pressure measurements to optimize the safety evaluation of noncardiovascular drugs with potential for hemodynamic effects: a report from the SYNERGY trial. Issue 3 (June 2018) - Weber, Michael A.; Chapple, Christopher R.; Gratzke, Christian; Herschorn, Sender; Robinson, Dudley; Frankel, Jeffrey M.; Ridder, Arwin M.; Stoelzel, Matthias; Paireddy, Asha; van Maanen, Robert; White, William B.
Abstract : Objective: The aim of this study was to perform a blood pressure (BP) safety evaluation in patients with an overactive bladder receiving solifenacin (an antimuscarinic agent), mirabegron (a β3 -adrenoceptor agonist), or both compared with placebo in the SYNERGY trial. Patients and methods: Patients were randomized to receive solifenacin 5 mg+mirabegron 50 mg (combination 5+50 mg); solifenacin 5 mg+mirabegron 25 mg (combination 5+25 mg); solifenacin 5 mg; mirabegron 50 mg; mirabegron 25 mg; or placebo for a double-blind 12-week treatment period. Systolic BP, diastolic BP, and heart rate were measured by ambulatory BP monitoring, and in the clinic or home. Results: A total of 715 patients were analyzed in an ambulatory BP monitoring substudy. At the end of treatment, ambulatory BP monitoring measurements showed no consistent increases from baseline in the mean 24-h systolic BP or diastolic BP for combination versus monotherapy groups or for monotherapy groups versus placebo. Analysis of 1-h BP averages during the 6 h range that included the T max values of both study drugs showed no significant BP effects. Shift analysis (switch between different normotension/hypertension stages) did not show differences among the active and placebo groups, nor did outlier analysis of major BP changes differ between placebo and active treatment. Similarly, there were no significant signals in the 24-h heart rate. Office and home measurements were consistent with ambulatory BP monitoring findings. Conclusions: A paradigm of ambulatory BP monitoring analysis designed to test BP safety of noncardiovascular drugs showed that solifenacin plus mirabegron combination therapy during 12 weeks produced no meaningful changes in BP or heart rate. Abstract : Supplemental Digital Content is available in the text.